Metal-polyphenol polymer modified polydopamine for chemo-photothermal therapy - Xu, Li; Luo, Zhibing; Liu, Qing; Wang, Chuancui; Zhou, Fei; Zhou, Min (Frontiers in Chemistry, 2023)
Chemotherapy combined with photothermal therapy (PTT) is a new way to improve the curative effect of cancer treatment. Here, we developed a multifunctional nanoparticle, namely PTX@mPDA@Fe-GA with the loading of a chemotherapeutic drug paclitaxel (PTX) for targeted and synergistic chemotherapy/photothermal therapy in lung cancer. Fe-gallic acid (Fe-GA) was coated on the surface of mesoporous polydopamine (mPDA) nanoparticles, and then the PTX was placed in the mesopores. The drug release of the loaded PTX exhibited pH- and thermal-dual responsive manner. Both mPDA and Fe-GA have high photothermal conversion ability and play a role in photothermal therapy. In addition, the results revealed that mPDA@Fe-GA had excellent biocompatibility and low hemolysis rate. The PTX-loaded mPDA@Fe-GA not only has excellent killing effect on lung cancer cells (A549) in vitro, but also can significantly suppress the growth of A549 subcutaneous tumor in nude mice. In a nutshell, the developed multifunctional nanoparticles integrate photothermal therapy and efficient chemotherapeutic drug delivery, providing new therapeutic ideas in the fight against lung cancer.